Antifungal Activity of Aspirin Derivatives against Sclerotinia sclerotiorum - Wang, Xuesong; Feng, Hui; Wang, Ling; Tang, Xiaorong (Asian Journal of Chemistry, 2013)
Two aspirin derivatives [2-(4-methylphenylcarbamoyl)phenyl acetate and 2-(4-methoxyphenylcarbamoyl)phenyl acetate] were synthesized by the ammonolysis of 2-(chlorocarbonyl)phenyl acetate. Their structure was confirmed by IR and 1H NMR. Their antifungal activity against Sclerotinia sclerotiorum has been determined in the laboratory. Results showed that they had good antifungal activity against Sclerotinia sclerotiorum. Their median effective concentrations (EC50) were 19.1 and 23.4 mg L-1, respectively.